Exploring the Impact of Islamic Leadership, Work Ethic, and Discipline on Job Satisfaction and Teacher Performance in Madrasah - Aceh, Ardi Saputra; Asnawi, Nur; Tharaba, M Fahim (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2024)
This study aims to analyze the influence of Islamic leadership, Islamic work ethic, work discipline, and job satisfaction on the success of teacher performance. The approach used is quantitative with a correlational type. The study population consisted of 185 teachers, with a sample of 126 teachers selected through a simple random sampling technique using Google Forms distribution. Data were analyzed using SmartPLS V.3.29. The results showed that Islamic leadership did not significantly affect teacher performance. However, Islamic work ethic, work discipline, and job satisfaction positively and significantly affected teacher performance. Islamic leadership and work ethic significantly affected job satisfaction, while work discipline did not. Islamic leadership had an indirect positive effect on teacher performance through job satisfaction, while Islamic work ethic and work discipline did not have a significant effect through job satisfaction. Based on the study results, teacher performance is optimal. All variables tested showed a dominant positive effect on other variables. The researcher designed the Islamic Integrity Index (i3) model as a concept of teacher performance standards in improving professionalism to produce quality education.